A Systematic Review of Machine Learning in Substance Addiction - Zulkifli N.F.; Cob Z.C.; Latif A.A.; Drus S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Patient treatment; Healthcare industry; Machine learning methods; Open doors; Systematic Review; Machine learning